A VISUAL NARRATIVE STRUCTURE ANALYSIS OF INDONESIAN HORROR WEBTOON IN EVOKING FEAR - Mawla Fatha, Basyarayni
Through decades, people have tried to reflect their thoughts, views, and realities that occur in a certain environment or time they aim to represent through comics. Such reflection on abstract values and views derived from people’s cultural beliefs is implicitly shown on the cultural products they create. This certainly does not exempt Indonesians with their own unique values, thoughts, and beliefs regarding their preference for certain genres depicted in the media they consume, horror webtoon is one of them. The appeal and popularity of horror media in Indonesia have been explicated as a close relation to the psyche of Indonesian people which is generally inherent to the Eastern culture. A certain tendency Indonesian readers express towards certain narratives that highlight a discrete set of local mysticism subthemes, (that includes but is not limited to ghosts, curses, shamanism, local superstitions, etc.) justifies this notion. Webtoon has an entirely different structure compared to the printed medium as a medium that utilizes the major characteristic of digital technologies through internet networks, even though webtoon itself is still classified as sequential art. This study aims to analyze how the visual narrative structure of Indonesian horror webtoon evoke fears within the readers’ minds and draw them into a dimension of engaging and ceaseless horror. This research focuses on using pieces of literature as its main source of justifiable argumentations to provide reasonable explanations. The object of study of this research is represented by three Indonesian horror webtoons taken from two series that were selected based on a specific pattern of readers’ preferences in Indonesian horror webtoon. These three selected objects applied different narrative and visual approaches to one another to avoid any bias occurring in the results. The Zpalanzani-Tabrani and Cohn triangulation analysis model is applied as an analytical methodology to determine the intangible aspects of the narrative, the tangible aspects of the visualization, and the sequential aspects related to the sequence of events and the arrangement of scenes in the panels to form a unified narrative. Several units of analysis such as the analysis of gutter space, the analysis of colors, and the affective responses that arise from the discourse structure are also added to the triangulation analysis model to adjust the methodology with the object of research considering the unique structure of the webtoon itself. The Zpalanzani-Tabrani and Cohn triangulation analysis model is a further development of the Zpalanzani triangulation analysis model that was initially used to analyze the visual narrative structure of Indonesian girl's comics. The result of this analysis suggests that there are idiomatic similarities between horror webtoons and horror films, both in terms of visual composition, visual units, and in terms of sequences in building the horror. The gutter space takes a pivotal part in forming a slow pace -or what is known as “alih slow motion” in Tabrani's visual grammar principle to trigger the state of suspense. This special approach certainly cannot be achieved by conventional printed comics because of the major difference in structures of both media